NILAI KEARIFAN LOKAL PANCASILA DALAM PERMAINAN TRADISIONAL ANAK: BENTENGAN: Refleksi Filosofis Manusia Sebagai Homo Ludens - Mayolla, Innoccentius Gerardo (Aggiornamento, 2024)
This study aims to 1) explore the values of local wisdom Pancasila in the children's game "Bentengan" and 2) reflect on the traditional children's game "Bentengan" in the light of the philosophy that humans are Homo Ludens. The children's game "Bentengan" is one of the traditional games of East Java. Bentengan is played collectively between more than three children. Axiologically, this game has a positive character education value for children's growth and development. Due to the characteristics of this locality, “Bentengan” also contains the value of local wisdom. The methodology that I used is a philosophical-phenomenological research study with an in-depth literature study of the writings on “Bentengan”. The results are then analyzed by philosophical reflection in the light of the local wisdom of Pancasila and the thoughts of John Huizinga, Homo Ludens (Humans are creatures who play). This study found that 1) the traditional children's game "Bentengan" contains the values of local wisdom Pancasila which is positive for children's growth and development and the development of Pancasila profiles for students 2) this local game contains human anthropological characters as creatures who play, namely expressing human freedom, symbolization of human struggle, temporality-spatiality, following the rules, self-purposed game (pursuit of happiness).